Small-Sided Game Training Using The Pyramid Principle to Increase Aerobic Endurance - Heryanto, Mamat; Sholehudin, Indra; Fadli, Muhamad (Journal of Physical and Outdoor Education, 2025)
Objectives of the research This For know influence exercise small-sided games to improvement ability aerobics with apply pyramid principle. Research This conducted at the Academy Persib U- 18 2024. Methods used in study This is experimental method with design in research This that is Pre-Experimental Design with pattern (pre-test, post-test design), and carried out technique taking sample using the Random assignment technique. The results of study This existence significant influence to improvement ability aerobics with use pyramid principle of 6% of the pre-test and post-test and obtained The sig value is 0.001 so there is significant influence method exercise small-sided games with use pyramid principle. Based on the data obtained researchers is existence significant influence method exercise small-sided games with use pyramid principle against improvement ability Power stand aerobics.